2020
DOI: 10.21203/rs.3.rs-21973/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How effective are digital interventions in increasing flu vaccination amongst pregnant women? A systematic review protocol

Abstract: Background: Pregnant women and their unborn babies are at increased risk of complications as a result of flu, yet uptake of the flu vaccination in the UK remains low. Digital interventions have proven effectiveness in changing health behaviour, but their effectiveness in increasing flu vaccination amongst pregnant women has not been examined. This protocol details the design and methodology of a systematic review and meta-analysis, examining the effectiveness of digital interventions in increasing flu vaccinat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…They also often believed that the vaccination could cause ill-health, and that it was a live vaccine. 39 This informed determinants that the animation will target in an attempt to change risk and efficacy appraisals, and subsequently increase the uptake of flu vaccination in this population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They also often believed that the vaccination could cause ill-health, and that it was a live vaccine. 39 This informed determinants that the animation will target in an attempt to change risk and efficacy appraisals, and subsequently increase the uptake of flu vaccination in this population.…”
Section: Resultsmentioning
confidence: 99%
“…Participants also felt that the animation was likely to increase pregnant women’s intentions to take up the offer of the flu vaccination. 39 There were minor changes identified as a result of the acceptability testing, such as changes to colouring of background and characters within the animation, and ordering of the animation, which resulted in a final round of amendments and minor changes being made.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The content and the messages within the animation were informed by a qualitative study, which identified knowledge gaps across a sample of 24 pregnant women recruited from community and hospital settings. This qualitative research identified that pregnant women underestimate their vulnerability to flu, underestimate the severity of flu to themselves and their unborn baby, and identified that pregnant women thought the flu vaccination was a live vaccine ( Parsons, 2019 ). The animation was designed to target all of these knowledge gaps.…”
Section: Development Of the Interventionmentioning
confidence: 99%